FIELD BASED ASSESSMENT OF FOLIAR BLIGHTS DISEASE OF WHEAT (Triticum aestivum L.) - Basnet, Roshan; Upadhyay, Shesh Raman; Gautam, Nutan Raj; Puri, Ramesh Raj; Pandey, Deepak (International Journal of Environment, 2015)
Wheat, the third major staple crop of Nepal has been suffered from many diseases. Various diseases are the major limiting factors of considerable wheat production, one of them is Spot blotch. Spot blotch caused by Bipolaris sorokiniana is a major disease of wheat in warm and humid regions of the Nepal. The fungus has a worldwide distribution but as a pathogen it is the most aggressive under the conditions of high relative humidity and temperature associated with the low fertility of soils in South Asia, South America, Africa, and Australia. The yield loss due to the disease is very significant Nepal. This experiment was conducted to identify the genotypes (crossing) having good level of resistance against spot blotch. The experiment set was received from CIMMYT comprises 52 entries and arranged in alpha lattice design with two replication in 2012/13 at NWRP, Bhairahawa condition. Three times diseases scoring were done in double digit method and calculated the Area under disease progress curve (AUDPC). Heading days, days to maturity, plant height and test weight were found highly significant but the grain yield and AUDPC were not significant among the entries. However, the grain yield and test weight (50.5 gm) were found higher where the AUDPC was lower recorded in genotype 6719 (4046 kg/ha and AUDPC 488.33) followed by genotype 6737 (3765 Kg/ha and AUDPC 576.9) and genotype 6718 (3550 kg/ha and AUDPC 596.33). International Journal of Environment Volume-4, Issue-3, June-August 2015Page: 140-150